2012 IEEE RO-MAN: The 21st IEEE International Symposium on Robot and Human Interactive Communication 2012
DOI: 10.1109/roman.2012.6343805
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the goal of an approaching agent: A human-robot study

Abstract: Abstract-The ability to infer intentions and predict actions enables coordinating of one's own actions with those of another human and allows smooth and intuitive interaction. The aim to achieve equally effective human-robot interactions is a crucial aspect of current robotic studies. Thus, we assume that studying human-human interaction provides valuable insights allowing to implement mutual intention recognition and action prediction in robotic systems. A common scenario of interaction, be it in everyday lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The observed stereotypical sequence of events is also compatible with a mechanism for social interactions suggested by Goffman (1971), who proposes a three-step process for interaction, comprising externalization (i.e., the choice of own actions so that the underlying intention can be recognized by others), scanning (i.e., the attempt to deduce others' intentions from their actions), and minimization of adjustment (i.e., the adaption of one's own plans to accommodate interference from nearby agents in such a way that adjustment with respect to the original plan is minimized). This is in line with our observations, namely that the person giving way waits for the other person to initiate a path adjustment and, upon seeing this, infers (Basili et al, 2012;Blake & Shiffrar, 2007) that the other person intends to cross first and, thus, adjusts their own trajectory to give way. By doing so, the risk of a conflicting role assignment is reduced and path adjustments can be minimized.…”
Section: Discussionsupporting
confidence: 90%
“…The observed stereotypical sequence of events is also compatible with a mechanism for social interactions suggested by Goffman (1971), who proposes a three-step process for interaction, comprising externalization (i.e., the choice of own actions so that the underlying intention can be recognized by others), scanning (i.e., the attempt to deduce others' intentions from their actions), and minimization of adjustment (i.e., the adaption of one's own plans to accommodate interference from nearby agents in such a way that adjustment with respect to the original plan is minimized). This is in line with our observations, namely that the person giving way waits for the other person to initiate a path adjustment and, upon seeing this, infers (Basili et al, 2012;Blake & Shiffrar, 2007) that the other person intends to cross first and, thus, adjusts their own trajectory to give way. By doing so, the risk of a conflicting role assignment is reduced and path adjustments can be minimized.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, we found that the significant differences in participant scores for each video are consistent with the existing literature about the methods to achieve legible robot behaviors [15]. In particular, to generate legible robot behaviors, the following variables were proposed: human-like behavior ( [51], [52]); stereotypical motions of everyday activities (e.g., reaching for an object) ( [51], [53]); the addition of complementary gestures to clarify intentions (e.g., gaze, pointing) ( [54], [55]); and the greatest possible visibility of the robot motion ( [56], [57]). We agree that these variables reported may have played a role in the scores.…”
Section: Discussionsupporting
confidence: 68%
“…While predictability is an important concept to human-robot interactions, there is no common understanding about the concept of predictability and there are various ways to approach this concept-it is an umbrella concept. Predictability is used in terms of it being a property of robotic motion [4,23,24,55,61,93]. In this context, the predictability of a motion relates to how well it matches the person's prediction regarding the robot's motion trajectory, given that the goal of the robot is known [23].…”
Section: Introductionmentioning
confidence: 99%